A paisagem em foco: leituras fotográficas de Jardim do Seridó-RN - Melo, Evaneide Maria (2008)
Landscape one of the main concepts in Geography can be understood as social practice and also as a form of spatial representation. In any case, it is necessary to understand it not only by it s visual instance though its visual instance is an important part of its own identity , but also as a signifying system that produces meaning through many forms of representation. Within this framework, the photographic image is an alternative field for the building, elaboration, re-elaboration and perception of the landscape. Within this context, the main objective of this work is to produce an understanding of Jardim do Seridó s landscape through the reading of its simbolic text built through the photographs taken by José Modesto de Azevedo, a photographer well known as Zé Boinho , in the period from 1950 to 1980. The way in which a specific representation of a particular geography works within the photographic paradigm, considering the narrative construction of urban space and landscape, constitutes the framework from which the concept of landscape is built. So, this work has taken into consideration the writings of authors such as Aumont (1993), Dondis (1997), Cosgrove (1998), Duncan (2004) e Shama (1996), Castoriadis (1982), etc. Thus, this work aimed to highlight that the urban space photographs narrative built by Zé Boinho is an important alternative field for the understanding of how Jardim do Seridó s landscape became a symbolic representation for the collective imaginary of the city